Would you like to participate in this trial? The practice of informed consent in intrapartum research in the last 30 years - Widmer, Mariana; Bonet, Mercedes; Betrán, Ana Pilar (PLOS ONE, 2020)
Background Informed consent is the cornerstone of the ethical conduct and protection of the rights and wellbeing of participants in clinical research. Therefore, it is important to identify the most appropriate moments for the participants to be informed and to give consent, so that they are able to make a responsible and autonomous decision. However, the optimal timing of consent in clinical research during the intrapartum period remains controversial, and currently, there is no clear guidance. Objective We aimed to describe practices of informed consent in intrapartum care clinical research in the last three decades, as reported in uterotonics for postpartum haemorrhage prevention trials. Methods This is a secondary analysis of the studies included in the Cochrane review entitled “Uterotonic agents for preventing postpartum haemorrhage: a network meta-analysis” published in 2018. All the reports included in the Cochrane network meta-analysis were eligible for inclusion in this analysis, except for those reported in languages other than English, French or Spanish. We extracted and synthesized data on the time each of the components of the informed consent process occurred. Results We assessed data from 192 studies, out of 196 studies included in the Cochrane review. The majority of studies (59.9%, 115 studies) reported that women were informed about the study, without specifying the timing. When reported, most studies informed women at admission to the facility for childbirth. Most of the studies reported that consent was sought, but only 59.9% reported the timing, which in most of the cases, was at admission for childbirth. Among these, 32 studies obtained consent in the active phase of labour, 17 in the latent phase and in 10 studies the labour status was unknown. Women were consented antenatally in 6 studies and in 8 studies the consent was obtained indistinctly during antenatal care or at admission. Most of the studies did not specified who was the person who sought the informed consent. Conclusion Practices of informed consent in trials on use of uterotonics for prevention of postpartum haemorrhage showed variability and substandard reporting. Informed consent sought at admission for childbirth was the most frequent approach implemented in these trials.